OPTIMIZATION STRATEGY OF CASH WAQF LINKED SUKUK INSTRUMENT FOR PROCUREMENT OF HEALTH FACILITIES IN INDONESIA - Ismi Siti Rabbani; Aas Nurasyiah; Rida Rosida; Abdul Ghafar Ismail (Universitas Airlangga, 2023)
This study aims to identify problems, solutions, and strategies that hinder the use of Cash Waqf Linked Sukuk (CWLS) as an instrument for procuring health facilities in Indonesia as seen from the dimensions of waqif, promotion, government, regulation, and nadzir. The data analysis technique used is the Analytic Network Process (ANP), using seven expert respondents from academics, regulators, and practitioners. The results of this study indicate that the priority dimension of problems and solutions in general in the use of the CWLS instrument for the procurement of health facilities in Indonesia has to do with the promotional dimension. This is because promotion is a means of communicating to the public about the CWLS instrument. Therefore, promotional activities can minimize people who do not know about the CWLS instrument. The overall strategic priority is the implementation of waqf literacy classes by the Ministry of Religion and the Indonesian Waqf Board to the community. Literacy is an essential component in influencing someone to contribute to waqf. Thus, with this strategy, it is hoped that the public will know about the CWLS instrument. This research is expected to provide benefits for stakeholders of the CWLS instrument to evaluate the strategies that have been carried out previously so that in the future, the utilization of the CWLS instrument in the health sector is more optimal, and the role of waqf in economic development can be achieved.